Outcomes of Open Surgery for Popliteal Artery Aneurysms: An 18-Year Experience in a Single Institution in Japan - Makino, Yoshihisa; Hoshina, Katsuyuki; Yamamoto, Kota; Kimura, Masaru (Scientific Research, 2018)
Objective: To elucidate the outcomes of open surgery for popliteal artery aneurysm (PAA) in a single Japanese institution. Materials and Methods: Between 1999 and 2016, 35 patients (44 PAAs) underwent open surgery in our department. The first-line surgical strategy involved the medial approach, with excision of the aneurysm sac and autologous vein bypass grafting. Associations between the outcomes and 1) the surgical management of the aneurysmal sac (aneurysmectomy vs. ligation with bypass) and 2) the preoperative clinical symptoms were evaluated. Results: There were no aneurysm-related deaths during the follow-up period (mean, 4 years; range, 1 - 17.6 years). The 5-year primary, primary-assisted, and secondary patency rates were 67.9%, 72.7%, and 94.5%, respectively. Re-intervention was required for 19 PAAs (14 patients), including two PAAs in patients with suspected Behçet’s disease. Patency rates did not differ between the aneurysmectomy and ligation groups. Remnant sac enlargement occurred in 3 cases. Among asymptomatic patients, clinical symptoms did not deteriorate; however, the ankle brachial pressure index decreased ≥0.15 in patients with artery-graft mismatching. Conclusion: Patency rates were good, and our modified ligation with bypass procedure, which involves excising the sac as much as possible, exhibited less risk in terms of remnant sac enlargement compared to that in previous studies
Keywords: Popliteal Artery Aneurysm; Approach; Bypass; Behçet’s Disease